ANALISIS ALIRAN DAYA SISTEM KELISTRIKAN 150 KV BALI SAAT REKONDUKTORING SUTT GILIMANUK – NEGARA – ANTOSARI - M.K. Huda; W.G. Ariastina; I W. Sukerayasa (Jurnal SPEKTRUM, 2020)
The need for electricity that is growing rapidly on the island of Bali, makes PT PLN (Persero)seek strategic steps in serving customers. Gilimanuk - Negara - Antosari Reconductoring SUTT150 kV is one of the efforts made by PT PLN (Persero) to improve the reliability of the BaliElectricity System which is used to overcome power evacuation problems in the future.Reconductoring goes through a one-month trip phase in each circuit. For this reason, a study isneeded to identify the electricity system readiness by using a power flow analysis simulatorapplication.The simulation is done by extinguishing each of the 150 kV conductors in the BaliElectricity System alternately by taking into account four scenario namely before conducting areconductor, reconductor circuit 1, reconductor circuit 2, and after reconductor. Voltagerecording is carried out on each bus with a tolerance of + 5% Vnom, recording of the load iscarried out on each active 150 kV conductor with a maximum capacity of 80% Inom. The resultsof the simulation show that the anomaly is only obtained when the simulation of circuit 1reconductor works if SUTT 150 kV Gilimanuk - Celukan Onion trip, causing a load exceeding80% Inom on SUTT 150 kV Gilimanuk - Pemaron and SUTT Gilimanuk - Negara - Antosari 2.